PENGARUH TRANSFER DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP KINERJA FISKAL PEMERINTAH DAERAH JENEPONTO DI PROVINSI SULAWESI SELATAN - Herlinah Herlinah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
The research was conducted at the local government Jeneponto aims to demonstrate empirically the effect of general allocation funds transfer and special allocation funds to the local government fiscal performance Jeneponto in South Sulawesi province partially and simultaneously. Type of this research is quantitative data and data sources of this research is secondary data, reports on realization of the district budget Jeneponto fiscal year 2013-2015. The analytical method used is multiple linear regression analysis, hypothesis testing and classical assumption. The results of this study indicate that the general allocation fund parisal positive influence on fiscal performance and the special allocation fund has positive influence on fiscal performance. Simultaneously the general allocation fund and special allocation funds positive influence on fiscal performance.